Desert sand curing agent as well as preparation method and use method thereof

By using modified slag and other components of desert sand curing agents in desert sand road construction materials, the problems of easy cracking and low mechanical properties of desert sand road construction materials are solved, and more efficient curing and durability are achieved.

CN119638306APending Publication Date: 2025-03-18FOSHAN TRANSPORTATION SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633149.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Desert sand has problems such as large shrinkage, low mechanical properties and easy cracking in road construction materials, especially in the dry climate and large temperature difference in the northwest region.

Method used

A desert sand curing agent is used, which includes slag, fly ash, cement, polymer fibers and modified slag. The modified slag is obtained by grafting lignin on the surface of the coal-fired slag, and is used to improve the moisture retention ability and mechanical properties of the curing agent.

Benefits of technology

This curing agent can effectively reduce drying and shrinkage, improve the mechanical properties and durability of desert sand, and is suitable for drying environments in the northwest region.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of curing agents, and particularly discloses a desert sand curing agent as well as a preparation method and a use method thereof. Wherein the desert sand curing agent comprises the following components in parts by weight: 10-30 parts of slag, 10-30 parts of fly ash, 5-20 parts of cement, 0.1-0.3 part of polymer fiber and 30-50 parts of modified slag; wherein the modified slag is obtained by grafting lignin on the surface of coal-fired slag. By implementing the curing agent, the mechanical property and durability of a curing material obtained by curing the curing agent can be improved, and the dry shrinkage is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of curing agents, and in particular to a desert sand curing agent and a preparation method and a use method thereof. Background Art

[0003] There are a series of problems when desert sand is used directly as road construction materials, including small particle size and smooth surface, which lead to large shrinkage and easy cracking of desert sand road construction materials, and mechanical properties are lower than those of ordinary concrete cementing systems. In addition, due to the dry climate in the northwest region, the temperature difference between day and night is large, and the water evaporates quickly, which leads to easy cracking and poor mechanical properties. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a desert sand curing agent which has small shrinkage and high strength and can realize efficient curing of desert sand.

[0005] Another technical problem to be solved by the present invention is to provide a method for preparing a desert sand curing agent.

[0006] The technical problem that the present invention needs to solve is to provide a method for using a desert sand curing agent.

[0007] In order to solve the above technical problems, the present invention provides a desert sand curing agent, which comprises the following components in parts by weight:

[0008] 10-30 parts of slag, 10-30 parts of fly ash, 5-20 parts of cement, 0.1-0.3 parts of polymer fiber, 30-50 parts of modified slag;

[0009] The modified slag is obtained by grafting lignin onto the surface of coal-fired slag.

[0010] As an improvement of the above technical solution, the preparation method of the modified slag is: coal-fired slag, lignin, and ethanol are mixed in a weight ratio of (30-50): (5-20): (40-60), reacted at 40°C to 100°C for 20-50 minutes, and dried.

[0011] As an improvement of the above technical solution, the coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler;

[0012] The content of SO3 in the coal-fired furnace slag is ≤2wt%, the content of CaO is ≤2wt%, and the total content of SiO2 and Al2O3 is ≥80wt%.

[0013] As an improvement of the above technical solution, the content of SO3 in the coal-fired furnace slag is 0.5-1.5wt%, the content of CaO is 0.5-1.5wt%, and the total content of SiO2 and Al2O3 is 82-90wt%.

[0014] As an improvement of the above technical solution, the coal-fired slag meets the following relationship:

[0015] LOI 1400 / LOI 800 =3~5;

[0016] LOI 800 -LOI 600 ≥0.55wt%;

[0017] Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600 It is the loss on ignition of coal-fired slag after being heated to 800°C under aerobic conditions and kept warm for 1 to 2 hours.

[0018] As an improvement of the above technical solution, the fly ash is high-calcium fly ash, the mullite content of which is ≤15wt% and the glass content is ≥80wt%.

[0019] As an improvement of the above technical solution, the content of Al2O3 in the glass body is ≤20wt%, and the total content of Na2O, K2O, CaO and MgO is ≥15wt%.

[0020] As an improvement of the above technical solution, the content of Al2O3 in the glass body is 10-20wt%, and the total content of Na2O, K2O, CaO and MgO is 20-35wt%.

[0021] Correspondingly, the present invention also discloses a method for preparing a desert sand curing agent, which is used to prepare the above-mentioned desert sand curing agent, and comprises: preparing modified slag, mixing the modified slag, slag, fly ash, cement and polymer fiber to obtain the obtained product.

[0022] Correspondingly, the present invention also discloses a method for using a desert sand curing agent, which is used to use the above-mentioned desert sand curing agent, and comprises:

[0023] Mixing a desert sand curing agent, desert sand to be cured, and water to obtain a slurry, wherein the water content of the slurry is 40-60wt%, and the content of the desert sand curing agent in the slurry is 15-25wt%;

[0024] The slurry is poured.

[0025] The implementation of the present invention has the following beneficial effects:

[0026] The desert sand curing agent of the present invention comprises the following components in parts by weight: 10 to 30 parts of slag, 10 to 30 parts of fly ash, 5 to 20 parts of cement, 0.1 to 0.3 parts of polymer fiber, and 30 to 50 parts of modified slag; wherein the modified slag is obtained by grafting lignin on the surface of coal-fired slag. Among them, the modified slag can effectively retain moisture and reduce volatilization, so that it is gradually released during the hydration process, improves the mechanical properties, and reduces the drying shrinkage of the curing agent when curing desert sand. The polymer fiber can play a bridging role and improve the mechanical properties of the cementitious system. Fly ash, slag, cement and modified slag can be used as active substances to generate cementitious materials, realize the fixation of desert sand, and at the same time improve the strength and durability of the cured material. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described below in conjunction with specific embodiments.

[0028] The present invention provides a desert sand curing agent, which comprises the following components in parts by weight:

[0029] 10-30 parts of slag, 10-30 parts of fly ash, 5-20 parts of cement, 0.1-0.3 parts of polymer fiber, 30-50 parts of modified slag;

[0030] Among them, the modified slag is obtained by grafting lignin on the surface of coal-fired slag. Coal-fired slag is slag produced by coal combustion, and its particle size is generally 0.5 to 10 mm, with a loose porous structure and a certain water retention effect. Furthermore, by grafting lignin on the surface of coal-fired slag, its water retention function can be further improved, reducing water volatilization, so that water is gradually released during the hydration process, improving mechanical properties, and reducing the drying shrinkage of the curing agent when curing desert sand. Specifically, lignin can be connected to the surface of coal-fired slag through a silane coupling agent, but is not limited to this.

[0031] Preferably, in some embodiments, the preparation method of the modified slag is: mix coal-fired slag, lignin, and ethanol in a weight ratio of (30-50): (5-20): (40-60), react at 40°C to 100°C for 20-50 minutes, and dry.

[0032] Specifically, the coal-fired slag can be solid waste generated during the combustion of coal in a pulverized coal furnace, or can be solid waste discharged from the combustion of coal in a circulating fluidized bed boiler, but is not limited thereto. Preferably, the coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler, and the residual carbon content of such coal-fired slag is relatively low, which can improve the overall workability of the curing agent and avoid excessive water absorption of residual carbon, resulting in poor workability of the curing system.

[0033] It should be noted that during the combustion process, the circulating fluidized boiler bed will increase calcium desulfurization in the furnace or desulfurize outside the furnace. The in-furnace desulfurization process will lead to an increase in the content of dihydrate gypsum. In this embodiment, it is more preferred to use coal-fired slag produced by the desulfurization process outside the furnace, which has a low content of dihydrate gypsum, which is conducive to improving the resistance to sulfate and carbonate erosion and damage, and improving the durability of the curing agent. Specifically, the chemical composition of the coal-fired slag has a content of SO3≤2wt%, a content of CaO≤2wt%, and a total content of SiO2 and Al2O3≥80wt%. It should be further noted that since desert sand belongs to salt rock sand, it often contains sulfates and carbonates, which will corrode the curing agent, causing the cured material to crack, erode, and even lose strength. Especially in the case of large areas of saline soil in the northwest region, this phenomenon is more obvious, which poses a serious threat to the durability and safe use of the curing agent. The inventors found during the experiment that when there are more gypsum phases in the formula system, in a high sulfate environment, the solidified material will continue to generate ettringite phases during use. Although ettringite can improve the solidification strength in the early and middle stages of solidification, the increasing amount of ettringite will also greatly increase the volume of the solidified material, causing the solidified material to fail. To this end, this embodiment controls the content of SO3 and CaO and the total content of SiO2 and Al2O3, so that the content of dihydrate gypsum in the coal-fired furnace is low, thereby improving the durability of the solidified material.

[0034] Further preferably, the content of SO3 in the coal-fired furnace slag is 0.5-1.5wt%, the content of CaO is 0.5-1.5wt%, and the total content of SiO2 and Al2O3 is 82-90wt%.

[0035] Further preferably, the coal-fired slag meets the following relationship:

[0036] LOI 1400 / LOI 800 =3~5;

[0037] LOI 800 -LOI 600 ≥0.55wt%;

[0038] Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600It is the loss on ignition of coal-fired slag after being heated to 800°C under aerobic conditions and kept warm for 1 to 2 hours. It should be noted that, firstly, coal-fired slag is often piled in the open air, and the CaO active component therein will react with water to form calcium hydroxide. Coal-fired slag with a high calcium hydroxide content will also generate short columnar gypsum under the erosion of high sulfates, reducing the durability of the solidified material. Secondly, the residual carbon in the coal-fired slag will absorb a large amount of water, reducing the workability of the solidified material. To this end, the present invention controls the loss on ignition of coal-fired slag at various temperatures to improve the durability and workability of the solidified material.

[0039] The amount of modified slag is 30 to 50 parts, exemplarily 32 parts, 36 parts, 40 parts, 44 parts or 48 parts, but not limited thereto, preferably 35 to 45 parts.

[0040] Among them, fly ash is solid waste collected in the flue gas after coal combustion, which has strong activity and can be hydrated to improve strength. Preferably, in one embodiment, the fly ash is high-calcium fly ash, and its mullite content is ≤15wt%, and its glass content is ≥80wt%. This fly ash has higher activity, which is beneficial to improving the mechanical properties of the solidified material. Specifically, the content of glass in the fly ash can be measured by corroding the fly ash with hydrofluoric acid, and the content of mullite in the fly ash can be obtained by measuring the fly ash after hydrofluoric acid corrosion by X-ray diffraction. It should be noted that in conventional fly ash, part of the alumina component will exist in the form of mullite, which has poor activity and will not participate in the gelling reaction. This embodiment uses high-calcium fly ash, which has low mullite content, high glass content, strong activity, and is beneficial to improving the mechanical properties of the solidified material.

[0041] Further preferably, the content of Al2O3 in the glass is ≤20wt%, and the total content of Na2O, K2O, CaO, and MgO is ≥15wt%. It should be noted that there are more cations such as Na2O, K2O, CaO, and MgO in this glass, which can act as network modifiers of the glass to produce more phase structures. The Si content in the glass is relatively low, which effectively improves the ability of the solidified material to resist carbonate and sulfate erosion at low temperatures. It should be noted that the inventors found in the research process that the temperature difference between day and night in the northwest region is large, and the temperature at night is often lower than 10°C. At low temperatures, carbonate ions and sulfate ions exist at the same time, which will cause the calcium silicate produced by hydration to be converted into carbon-sulfur-silicon-calcium, which has no cementing ability and will greatly reduce the mechanical properties of the solidified material. In this embodiment, the chemical composition of the glass is controlled to make the glass in the fly ash have more phase structures, that is, it is differentiated into multiple phases during the hydration process, such as calcite, quartz, tricalcium silicate, tricalcium aluminate, etc., reducing hydration in the form of amorphous hydrated calcium silicate, thereby greatly improving the ability to resist carbonate and sulfate erosion at low temperatures.

[0042] More preferably, the content of Al2O3 in the glass body is 10-20wt%, and the total content of Na2O, K2O, CaO and MgO is 20-35wt%.

[0043] Specifically, the amount of fly ash is 10 to 30 parts, exemplarily 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts or 28 parts, but not limited thereto, preferably 20 to 30 parts.

[0044] Among them, slag is a powder material obtained by grinding granulated blast furnace slag to a specified fineness. It has high potential activity and can undergo hydration reaction under alkaline excitation conditions to improve the mechanical properties of the desert sand curing agent. Specifically, the slag can be S95 grade or S105 grade, but not limited to this. Exemplarily, the amount of slag is 12 parts, 14 parts, 16 parts, 18 parts or 19 parts, but not limited to this. Preferably, it is 20 to 30 parts.

[0045] Among them, cement can bind the components in the desert sand curing agent. Specifically, the cement can be silicate cement or sulphoaluminate cement, but not limited thereto, preferably silicate cement. The strength grade of cement is 42.5 or 52.5, but not limited thereto. Specifically, the amount of cement is 5 to 20 parts, exemplarily 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts, but not limited thereto. Preferably, it is 5 to 15 parts.

[0046] The polymer fiber can play a bridging role and improve the mechanical properties of the gelling system. Specifically, the polymer fiber can be selected from polyvinyl alcohol fiber, polypropylene fiber, and polyurethane fiber, but is not limited thereto. The length of the polymer fiber is 2 to 15 mm, and its breaking strength is 500 to 1500 MPa.

[0047] The desert sand curing agent in the present invention may also include auxiliary components such as a water reducing agent and a defoaming agent, but is not limited thereto. The amount of the auxiliary agent can be selected according to the specific amount of water used, but is not limited thereto.

[0048] Correspondingly, in one embodiment of the present invention, a method for preparing a desert sand solidifier is also disclosed, which is used to prepare the above-mentioned desert sand solidifier, and includes: preparing modified slag, mixing the modified slag, slag, fly ash, cement, and polymer fiber.

[0049] Accordingly, in one embodiment of the present invention, a method for using a desert sand curing agent is also disclosed, which is used to use the above-mentioned desert sand curing agent, and comprises the following steps:

[0050] (1) mixing a desert sand curing agent, desert sand to be cured, and water to obtain a slurry;

[0051] The water content of the slurry is 40-60 wt %, and the content of the desert sand curing agent in the slurry is 15-25 wt %;

[0052] (2) pouring the slurry.

[0053] The present invention is described below with specific embodiments:

[0054] The density of the desert sand used in the following examples is 2645 kg / m 3 The fineness modulus is 0.11, the water absorption rate is about 4.25%, and its fine particles are mostly needle-shaped.

[0055] Example 1

[0056] This embodiment provides a desert sand curing agent, and its formula is as follows:

[0057] 30 parts of S95 slag, 30 parts of fly ash, 9.8 parts of PO42.5 cement, 0.2 parts of polyurethane fiber, and 30 parts of modified slag;

[0058] The fly ash is low-calcium fly ash, and its mullite content is 21.24wt%, its glass content is 72.5wt%, the Al2O3 content in the glass is 33.25wt%, and the total content of Na2O, K2O, CaO and MgO is 7.56wt%.

[0059] The preparation method of the modified slag is as follows: coal-fired slag, lignin and ethanol are mixed in a weight ratio of 40:10:50, reacted at 50°C for 30 minutes, and dried to obtain the modified slag.

[0060] The coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler, with an average particle size of 1 mm to 3 mm, a SO3 content of 4.95 wt%, a CaO content of 3.87 wt%, and a total content of SiO2 and Al2O3 of 81.35 wt%. 1400 =6.95wt%,LOI 800 =4.25wt%,LOI 600 =2.35wt%. Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400℃ under anaerobic conditions and keeping it warm for 2h. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 2 hours. 600 It is the loss on ignition of coal-fired slag after heating to 800℃ under aerobic conditions and keeping it warm for 2 hours.

[0061] The preparation method of the desert sand curing agent in this embodiment is: prepare modified slag, and mix the modified slag, slag, fly ash, cement, and polymer fiber to obtain the solidifying agent.

[0062] Example 2

[0063] This embodiment provides a desert sand curing agent, and its formula is as follows:

[0064] 25 parts of S95 slag, 28.5 parts of fly ash, 11.3 parts of PO42.5 cement, 0.2 parts of polyurethane fiber, and 35 parts of modified slag;

[0065] The fly ash is low-calcium fly ash, and its mullite content is 21.24wt%, its glass content is 72.5wt%, the Al2O3 content in the glass is 33.25wt%, and the total content of Na2O, K2O, CaO and MgO is 7.56wt%.

[0066] The preparation method of the modified slag is as follows: coal-fired slag, lignin and ethanol are mixed in a weight ratio of 40:10:50, reacted at 50°C for 30 minutes, and dried to obtain the modified slag.

[0067] The coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler, with an average particle size of 0.5 mm to 2 mm, a SO3 content of 1.51 wt%, a CaO content of 1.74 wt%, and a total content of SiO2 and Al2O3 of 86.74 wt%. 1400 =4.22wt%,LOI 800 =1.94wt%,LOI 600 =1.85wt%. Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400℃ under anaerobic conditions and keeping it warm for 2h. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 2 hours. 600 It is the loss on ignition of coal-fired slag after heating to 800℃ under aerobic conditions and keeping it warm for 2 hours.

[0068] The preparation method of the desert sand curing agent in this embodiment is: prepare modified slag, and mix the modified slag, slag, fly ash, cement, and polymer fiber to obtain the solidifying agent.

[0069] Example 3

[0070] This embodiment provides a desert sand curing agent, and its formula is as follows:

[0071] 25 parts of S95 slag, 28.5 parts of fly ash, 11.3 parts of PO42.5 cement, 0.2 parts of polyurethane fiber, and 35 parts of modified slag;

[0072] The fly ash is low-calcium fly ash, and its mullite content is 21.24wt%, its glass content is 72.5wt%, the Al2O3 content in the glass is 33.25wt%, and the total content of Na2O, K2O, CaO and MgO is 7.56wt%.

[0073] The preparation method of the modified slag is as follows: coal-fired slag, lignin and ethanol are mixed in a weight ratio of 40:10:50, reacted at 50°C for 30 minutes, and dried to obtain the modified slag.

[0074] The coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler, with an average particle size of 0.5 mm to 2 mm, a SO3 content of 1.38 wt%, a CaO content of 1.86 wt%, and a total content of SiO2 and Al2O3 of 85.78 wt%. 1400 =3.22wt%,LOI 800 =1.42wt%,LOI 600 =0.55wt%. Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400℃ under anaerobic conditions and keeping it warm for 2h. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 2 hours. 600 It is the loss on ignition of coal-fired slag after heating to 800℃ under aerobic conditions and keeping it warm for 2 hours.

[0075] The preparation method of the desert sand curing agent in this embodiment is: prepare modified slag, and mix the modified slag, slag, fly ash, cement, and polymer fiber to obtain the solidifying agent.

[0076] Example 4

[0077] This embodiment provides a desert sand curing agent, and its formula is as follows:

[0078] 25 parts of S95 slag, 28.5 parts of fly ash, 11.3 parts of PO42.5 cement, 0.2 parts of polyurethane fiber, and 35 parts of modified slag;

[0079] The fly ash is high-calcium fly ash, the mullite content of which is 3.51wt%, the glass content is 82.54wt%, the Al2O3 content in the glass is 18.59wt%, and the total content of Na2O, K2O, CaO and MgO is 31.13wt%.

[0080] The preparation method of the modified slag is as follows: coal-fired slag, lignin and ethanol are mixed in a weight ratio of 40:10:50, reacted at 50°C for 30 minutes, and dried to obtain the modified slag.

[0081] The coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler, with an average particle size of 0.5 mm to 2 mm, a SO3 content of 1.38 wt%, a CaO content of 1.86 wt%, and a total content of SiO2 and Al2O3 of 85.78 wt%. 1400 =3.22wt%,LOI 800 =1.42wt%,LOI 600 =0.55wt%. Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400℃ under anaerobic conditions and keeping it warm for 2h. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 2 hours. 600 It is the loss on ignition of coal-fired slag after heating to 800℃ under aerobic conditions and keeping it warm for 2 hours.

[0082] The preparation method of the desert sand curing agent in this embodiment is: prepare modified slag, and mix the modified slag, slag, fly ash, cement, and polymer fiber to obtain the solidifying agent.

[0083] Comparative Example 1

[0084] This comparative example provides a desert sand curing agent, which differs from Example 1 in that slag is not included, and the rest is the same as Example 1.

[0085] Comparative Example 2

[0086] This comparative example provides a desert sand curing agent, which differs from Example 1 in that fly ash is not included, and the rest is the same as Example 1.

[0087] Comparative Example 3

[0088] This comparative example provides a desert sand curing agent, which differs from Example 1 in that it does not include modified slag, and the rest is the same as Example 1.

[0089] Test Example 1

[0090] The desert sand curing agent, desert sand and water obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were mixed to obtain a slurry with a moisture content of 45wt%, and the content of the desert sand curing agent in the slurry was 20wt%. The slurry was molded into a cubic test mold of 70.7mm×70.7mm×70.7mm, and after curing for 28 days, its shrinkage value (refer to "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" JTG 3441-2024), unconfined compressive strength, and flexural strength (refer to "Test Method for Strength of Cement Mortar (ISO Method)" GB / T17671-2021 for testing) were tested respectively; and a freeze-thaw cycle test was carried out with reference to the "Highway Geotechnical Test Procedure" (JTG 3430-2020). During the test, the concentration of the sodium sulfate solution was 7wt%, and the concentration of the sodium carbonate solution was 5wt%.

[0091] The specific test results are as follows:

[0092]

[0093] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A desert sand curing agent, characterized in that: The composition comprises the following components in parts by weight: 10-30 parts of slag, 10-30 parts of fly ash, 5-20 parts of cement, 0.1-0.3 parts of polymer fiber, 30-50 parts of modified slag; The modified slag is obtained by grafting lignin onto the surface of coal-fired slag.

2. The desert sand curing agent according to claim 1, characterized in that: The preparation method of the modified slag is as follows: coal-fired slag, lignin and ethanol are mixed in a weight ratio of (30-50): (5-20): (40-60), reacted at 40°C-100°C for 20-50 minutes, and dried to obtain the modified slag.

3. The desert sand curing agent according to claim 1 or 2, characterized in that: The coal-fired slag is solid waste discharged from the combustion of a circulating fluidized bed boiler; The content of SO3 in the coal-fired furnace slag is ≤2wt%, the content of CaO is ≤2wt%, and the total content of SiO2 and Al2O3 is ≥80wt%.

4. The desert sand curing agent according to claim 3, characterized in that: The coal-fired furnace slag has a SO3 content of 0.5-1.5wt%, a CaO content of 0.5-1.5wt%, and a total SiO2 and Al2O3 content of 82-90wt%.

5. The desert sand curing agent according to claim 1 or 2, characterized in that: The coal-fired slag meets the following relationship: LAW 1400 / LAW 800 =3~5; LAW 800 -LAW 600 ≥0.55wt%; Among them, LOI 1400 LOI is the loss on ignition of coal-fired slag after heating to 1400°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600 LOI is the loss on ignition of coal-fired slag after heating to 600°C under anaerobic conditions and keeping it warm for 1 to 2 hours. 600 It is the loss on ignition of coal-fired slag after being heated to 800°C under aerobic conditions and kept warm for 1 to 2 hours.

6. The desert sand curing agent according to claim 1, characterized in that: The fly ash is high-calcium fly ash, the mullite content of which is ≤15wt%, and the glass content of which is ≥80wt%.

7. The desert sand curing agent according to claim 4, characterized in that: The content of Al2O3 in the glass body is ≤20wt%, and the total content of Na2O, K2O, CaO and MgO is ≥15wt%.

8. The desert sand curing agent according to claim 5, characterized in that: The content of Al2O3 in the glass body is 10-20wt%, and the total content of Na2O, K2O, CaO and MgO is 20-35wt%.

9. A method for preparing a desert sand curing agent, for preparing the desert sand curing agent according to any one of claims 1 to 8, characterized in that: include: The modified slag is prepared by mixing the modified slag, slag, fly ash, cement and polymer fiber.

10. A method for using a desert sand curing agent, for using the desert sand curing agent according to any one of claims 1 to 8, characterized in that: include: Mixing a desert sand curing agent, desert sand to be cured, and water to obtain a slurry, wherein the water content of the slurry is 40-60wt%, and the content of the desert sand curing agent in the slurry is 15-25wt%; The slurry is poured.